El fracaso en la resolución de problemas de Física : una investigación orientada por nuevos supuestos - Gil, D.; Martínez-Torregrosa y Senet, F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper shows an attempt to question the usual way of teaching problem solving and to elaborate more effective theoretically based proposats. Some results of the applications of new orientations are included.